Physical activity has decreased in Finnish children and adolescents from 2016 to 2022 - Pauliina Husu; Kari Tokola; Henri Vähä-Ypyä; Harri Sievänen; Sami Kokko; Jari Villberg; Tommi Vasankari (BMC, 2024)
Abstract Background Varying trends in children's and adolescents' physical activity (PA) have been reported during the last 10-20 years. Trends in sedentary behavior (SB) have been studied only rarely. The purpose of the present study was to describe population-based trends in accelerometer-measured PA, standing and SB, among Finnish 7-15-year-old children and adolescents, and to evaluate the potential influence of the COVID-19 pandemic on these behaviors. Method A cross-sectional population-based Finnish school-aged physical activity Study (FSPA) measured daily steps, vigorous (VPA), moderate (MPA), moderate-to-vigorous (MVPA), light physical activity (LPA), standing, and SB by an accelerometer for seven consecutive days in 2016, 2018, and 2022 (n = 7.080, 57% girls). The data was analyzed by multivariate regression analysis. Results In 2016, participants took on average 10.305 steps per day, and spent 0:15 (h: min) in VPA, 1:37 in MPA, 1:52 in MVPA, 3:48 in LPA, 0:55 in standing and 7:52 in SB. From 2016 to 2018, daily steps, MPA, LPA, and standing increased [229 steps (95% Confidence Interval, CI 70-387), 0:03 (CI 0:01 − 0:04), 0:11 (CI 0:09 − 0:14), and 0:07 (CI 0:05 − 0:08), respectively], while VPA and SB decreased [0:01 (CI 0:00-0:02) and 0:20 (CI 0:16 − 0:24), respectively]. From 2018 to 2022, daily PA and standing declined [751 steps (CI 562-939), VPA 0:02 (CI 0:01 − 0:03), MPA 0:09 (CI 0:07 − 0:11), MVPA 0:11 (CI 0:09 − 0:14), LPA 0:08 (CI 0:05 − 0:11), and standing 0:01 (CI 0:01 − 0:03)] while SB increased 0:21 (CI 0:16 − 0:25) indicating potential influence of the pandemic. Conclusions Children and adolescents became physically less active from 2016 to 2022. The potential effects of the COVID-19 were seen as declined PA and increased sedentariness from 2018 to 2022.